A Retrospective Study of Arabian Stallion Fertility Used in National Stud Farm of Tiaret (West of Algeria) - HOUSSOU Hind; BOUZEBDA AFRI Farida; BOUZEBDA Zoubir (IDOSI Publications, 2018)
The aim of this paper to evaluate the stallion fertility in advance and to aid breeding management. The collection of a historical information about the Arabian stallions adults (n=101) and 495 mares with range age between (8 and 26) years in the national stud farm of Chaouchoua Tiaret. Fertility was measured using three endpoints: foaling rates (FR), percent pregnant per cycle (PC) and percent pregnant per season (PR) during (2003-2013).The pregnant per season rate (PR) was of 84 % The foaling rate (FR) was of 80%, the pregnancy cycle rate (PC) was of 96 % ; a strong correlation existed between the number of mares mated and (PC) (r= -0.59; p<0.01). We conclude that breeding records existed in many forms (foaling, pregnancy per cycle, or per season rates), but there is still a need to develop tests that can predict fertility with a reasonable degree of certainty before the stallion has begun his breeding career.